2018
DOI: 10.21037/jtd.2018.07.09
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk of thromboembolism associated with bevacizumab in patients with non-small cell lung carcinoma

Abstract: Bevacizumab is associated with a significantly increased risk of thromboembolism development in NSCLC patients. It may have dose-toxicity relationship and low dose of bevacizumab may be a better choice for NSCLC patients, with equal efficacy and low hazard of thromboembolism events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…Gemcitabine and platinum-containing chemotherapy were the most commonly reported treatment-related prognostic factors for VTE. Similar to previous studies, [35][36][37] we found that the use of platinum-based compounds was associated with an increased risk of VTE across the included studies. The association between the use of gemcitabine and VTE was less conclusive, despite previous studies suggesting that this treatment increased the risk of VTE, 37,38 which may be explained by adjustment factors and potential confounding.…”
Section: Vegfa-1190g/asupporting
confidence: 88%
“…Gemcitabine and platinum-containing chemotherapy were the most commonly reported treatment-related prognostic factors for VTE. Similar to previous studies, [35][36][37] we found that the use of platinum-based compounds was associated with an increased risk of VTE across the included studies. The association between the use of gemcitabine and VTE was less conclusive, despite previous studies suggesting that this treatment increased the risk of VTE, 37,38 which may be explained by adjustment factors and potential confounding.…”
Section: Vegfa-1190g/asupporting
confidence: 88%
“…The incidence of treatment-related TE was 3.5% in our patients, which was lower compared with prior studies. 16,17,24 It may be that these studies did not classify TE as disease-or treatment-related. Moreover, proteinuria was an independent predictor of treatment-related TE.…”
Section: Discussionmentioning
confidence: 99%
“…The largest meta-analysis, which included 20,500 patients with multiple cancer types found an increased risk for ATE and VTE, but no subgroup analysis for cancer type was made [ 52 ]. In advanced lung cancer, a Chinese meta-analysis found an increased risk for all TEs (RR 1.74; 95% CI, 1.15–2.62) but did not make a subanalysis for VTE or ATE [ 53 ]. The increased risk was driven by the high-dose group (15 mg/m 2 Q3w), whereas the result in the low-dose group (7.5 mg/m 2 ) was not significant [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…In advanced lung cancer, a Chinese meta-analysis found an increased risk for all TEs (RR 1.74; 95% CI, 1.15–2.62) but did not make a subanalysis for VTE or ATE [ 53 ]. The increased risk was driven by the high-dose group (15 mg/m 2 Q3w), whereas the result in the low-dose group (7.5 mg/m 2 ) was not significant [ 53 ].…”
Section: Discussionmentioning
confidence: 99%